Avaliação do potencial imunoprotetor de antígenos recombinantes de Leptospira interrogans - Felix, Samuel Rodrigues (2009)
Leptospirosis is a disease caused by pathogenic spirochetes of the Leptospira genus. It is the most widespread zoonosis in the world, representing a veterinarian and public health problem especially in developing countries. From a veterinarian point of view, leptospirosis is important both as a medical problem, mainly in dogs, which can suffer the ailment as well as transmit it, and as an economic problem, mainly in cattle and pigs, where it causes direct production and reproductive losses. Vaccination of these animals is largely applied, however protection is limited. Conventional vaccines confer protection restricted to the sorovars present in the preparation and fail to protect against renal infection, allowing seemingly healthy animals to shed bacteria, and produce short term protection requiring frequent revaccination. The vaccines are also available for humans, but are used only in a few countries such as Cuba and China. The goal of this work was to test the immune protective potential of recombinant Leptospira interrogans proteins produced in Escherichia coli, using the hamster model. Twenty recombinant vaccine candidates were produced and inoculated in hamsters in two doses, fourteen days apart. Two weeks after the second dose all animals were challenged with 100 leptospires (~2xLD50). After the challenge, animals were observed daily for disease. Of all the proteins tested, seven protected animals to some extent, ranging from 16.7% to 50%. Two proteins presented promising results, and were recommended for further studies, as potential leptospira subunit vaccine candidates.